Relationship between Self-Adjustment toward Academic Procrastination among First-Year Students in the Bachelor of Nursing Program at Universitas Jember - Darodjadien Naofal Nabawi; Retno Purwandari; Alfid Tri Afandi; Nurfika Asmaningrum; Yulia Kurniawati (Universitas Tribhuwana Tunggadewi, 2025)
First-year students encounter academic, social, and emotional challenges that can impede their adjustment capacity. Inadequate adaptation frequently precipitates academic procrastination, which detrimentally affects academic achievement. Effective adjustment plays a significant role in mitigating task delay tendencies. This study examined the relationship between self-adjustment and academic procrastination among first-year Bachelor of Nursing students at Universitas Jember. This study employed a cross-sectional correlational design. A total of 168 first-year students were selected via total population sampling. Data were collected from April to May 2025 using the Student Adaptation to College Questionnaire to measure self-adjustment and the Procrastination Assessment Scale-Students to measure academic procrastination. Data were analyzed using Spearman-rank Correlation test with a significance level of ? = 0,05. Findings indicated that 72,6% of respondents exhibited a moderate level of self-adjustment, while 70,2% demonstrated moderate academic procrastination. Correlation analysis indicated a statistically significant result p-value of 0,000 (p 0,05). A correlation coefficient (r) of -0,503 indicated a moderate-strength and negative relationship. The results of the study showed a moderately significant relationship between the two variables of self-adjustment and academic procrastination with a negative correlation, meaning that the higher of self-adjustment, the lower of academic procrastination. Students with effective self-adjustment abilities tend to complete tasks more efficiently, thereby reducing their tendency to procrastinate. Self-adjustment is not the only factor influencing academic procrastination, other related factors also contribute to the persistence of procrastination behavior during the developmental stage of first-year students. Other variables and factors that influence academic procrastination in new students can be examined for further research